2019
DOI: 10.2147/idr.s196452
|View full text |Cite
|
Sign up to set email alerts
|

<p>Increase in antibiotic resistant <em>Helicobacter pylori</em> in a University Hospital in Japan</p>

Abstract: BackgroundEradication effectively prevents Helicobacter pylori-associated diseases; however, H. pylori antibiotic resistance has increased throughout Japan and worldwide. This study aimed to assess rates of resistance to antibiotics; amoxicillin, clarithromycin and metronidazole in a University Hospital in Japan.Materials and methodsH. pylori (208 strains) were isolated from patients at the Okayama University Hospital in Japan. The minimum inhibitory concentrations (MIC) were determined using the mean values o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 34 publications
5
36
0
Order By: Relevance
“…Some genetic determinants (e.g., N562Y, S414R, T593A, G595S, and A599T) have been reported using a classic approach, in which the limitation was demonstrated as discussed above. Because of the invalidity of these mutations in other studies, a recent paper by Chihiro K et al [53] concluded that AMX resistance determination should not be identified based on one amino acid substitution at a specific position. Our study found three AMX-resistant associated loci (P473L, E406K, and T593A/G/K mutations).…”
Section: Discussionmentioning
confidence: 99%
“…Some genetic determinants (e.g., N562Y, S414R, T593A, G595S, and A599T) have been reported using a classic approach, in which the limitation was demonstrated as discussed above. Because of the invalidity of these mutations in other studies, a recent paper by Chihiro K et al [53] concluded that AMX resistance determination should not be identified based on one amino acid substitution at a specific position. Our study found three AMX-resistant associated loci (P473L, E406K, and T593A/G/K mutations).…”
Section: Discussionmentioning
confidence: 99%
“…The individual studies detailing resistance are summarized in Table 1. [21][22][23][24][25][26][27][28][29][30][31][32]…”
Section: Antib I Oti C Re S Is Tan Cementioning
confidence: 99%
“…However, antibiotic resistance caused in Helicobacter pylori eradication failure and the resistance rates widely vary around the world [2][3][4]. Recent hospital-based study in Japan reporting 48% of clarithromycin resistance [5] while our previous study in Indonesia reported a 9% resistant rate [6]. Because of such differences, the Maastricht Consensus Report on H. pylori infection has stated that antibiotic susceptibility tests with periodic monitoring should be performed in each region to determine the most suitable therapy for a given population [2].…”
Section: Introductionmentioning
confidence: 97%